Impairment of the ER/mitochondria compartment in human cardiomyocytes with PLN p.Arg14del mutation. Issue 6 (16th May 2021) - Cuello, Friederike; Knaust, Anika E; Saleem, Umber; Loos, Malte; Raabe, Janice; Mosqueira, Diogo; Laufer, Sandra; Schweizer, Michaela; van der Kraak, Petra; Flenner, Frederik; Ulmer, Bärbel M; Braren, Ingke; et al.
Abstract: The phospholamban (PLN) p.Arg14del mutation causes dilated cardiomyopathy, with the molecular disease mechanisms incompletely understood. Patient dermal fibroblasts were reprogrammed to hiPSC, isogenic controls were established by CRISPR/Cas9, and cardiomyocytes were differentiated. Mutant cardiomyocytes revealed significantly prolonged Ca 2+ transient decay time, Ca 2+ ‐load dependent irregular beating pattern, and lower force. Proteomic analysis revealed less endoplasmic reticulum (ER) and ribosomal and mitochondrial proteins. Electron microscopy showed dilation of the ER and large lipid droplets in close association with mitochondria. Follow‐up experiments confirmed impairment of the ER/mitochondria compartment. PLN p.Arg14del end‐stage heart failure samples revealed perinuclear aggregates positive for ER marker proteins and oxidative stress in comparison with ischemic heart failure and non‐failing donor heart samples. Transduction of PLN p.Arg14del EHTs with the Ca 2+ ‐binding proteins GCaMP6f or parvalbumin improved the disease phenotype. This study identified impairment of the ER/mitochondria compartment without SR dysfunction as a novel disease mechanism underlying PLN p.Arg14del cardiomyopathy. The pathology was improved by Ca 2+ ‐scavenging, suggesting impaired local Ca 2+ cycling as an important disease culprit. Synopsis: The disease mechanism linking the phospholamban (PLN) p.Arg14del mutation to dilated cardiomyopathy is incompletely understood. In this study, patient‐derived human induced pluripotent stem cell‐cardiomyocytes were used to elucidate this molecular mechanism. Sarcoplasmic reticulum function remained unaltered in PLN p.Arg14del human cardiomyocytes. Impairment of the interface between endoplasmic reticulum and mitochondria was discovered as a novel disease phenotype. Cytoplasmic calcium‐scavenging improved the cardiomyopathy phenotype and revealed the role for cytoplasmic calcium in disease development. Abstract : The disease mechanism linking the phospholamban (PLN) p.Arg14del mutation to dilated cardiomyopathy is incompletely understood. In this study, patient‐derived human induced pluripotent stem cell‐cardiomyocytes were used to elucidate this molecular mechanism.